The Implications of Quarter-Life Crisis on Adolescent Character (Case Study of Students of the Faculty of Usuluddin and Islamic Thought) - Maida Alda Irma; Alfi Julizun Azwar; R.A. Erika Septiana (Al-Abqori: Journal of Islamic Thought Studies, 2026)
Quarter Life Crisis (QLC) is a phase of crisis commonly experienced by people in their 20s, characterized by confusion about the direction of life, anxiety about the future, and pressure to fulfill how QLC affects the character of adolescents, especially students of the Faculty of Ushuluddin and Islamic Thought. This study uses a descriptive quantitative method with a case study approach. The results of this study show that students experiencing QLC tend to exhibit symptoms such as indecision, decreased self-confidence, emotional pressure, and negative self-assessment. On the other hand, QLC can also encourage students to engage in deep self-reflection and spur the development of a more mature character. Internal factors such as the search for self-identity and external factors such as social and academic pressure are the main triggers for the emergence of QLC. This research emphasizes the importance of social support and spiritual approaches as preventive and solution-oriented measures in addressing QLC, as well as the need for character development in adolescents to enable them to navigate the transition toward adulthood in a healthier and more adaptive manner.